Principles of Sound Fertilizer Recommendations - George Hochmuth; Edward Hanlon (EDIS)
SL315, an 8-page fact sheet by G. Hochmuth and E. Hanlon, describes components of science-based recommendations (best management practices) for fertilizer management in modern vegetable production. Includes sources of additional information. Published by the UF Department of Soil and Water Sciences, February 2010.